1998
DOI: 10.1002/(sici)1521-3757(19980116)110:1/2<198::aid-ange198>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Totalsynthese von Altohyrtin A (Spongistatin 1): Teil 1

Abstract: Außerordentlich cytotoxisch sind die aus Meeresschwämmen isolierten Spongipyrane. Sie wirken gegen mehrere menschliche Krebszellinien, wobei das als erste Verbindung dieser Naturstoffklasse isolierte Spongistatin 1 am wirksamsten ist. Die erste Totalsynthese dieses Makrolids wurde nun abgeschlossen. Durch sie wird die von Kitagawa et al. vorgeschlagene relative und absolute Konfiguration bestätigt und nachgewiesen, daß Altohyrtin A und Spongistatin 1 identisch sind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 41 publications
0
1
0
1
Order By: Relevance
“…While Evans et al had previously reported the successful regioselective macrocyclization of a spongistatin seco‐acid, it is intriguing to note that the 23‐ epi ‐seco acid also displays the same ring size preference. Global deprotection (HF/CH 3 CN/H 2 O)14a then furnished both (+)‐spongistatin 2 ( 2 ) and the C(23) epimer ( 23 ) in 60–66 % yield, with the unnatural congener predominating (3:1) 16. Acid‐mediated epimerization of 23 in the presence of Ca 2+ ions led to a mixture of (+)‐spongistatin 2 ( 2 ) and (−)‐ epi ‐spongistatin 2 ( 23 ) in a ratio of 3.9–2.3:1 (ca.…”
Section: Methodsmentioning
confidence: 99%
“…While Evans et al had previously reported the successful regioselective macrocyclization of a spongistatin seco‐acid, it is intriguing to note that the 23‐ epi ‐seco acid also displays the same ring size preference. Global deprotection (HF/CH 3 CN/H 2 O)14a then furnished both (+)‐spongistatin 2 ( 2 ) and the C(23) epimer ( 23 ) in 60–66 % yield, with the unnatural congener predominating (3:1) 16. Acid‐mediated epimerization of 23 in the presence of Ca 2+ ions led to a mixture of (+)‐spongistatin 2 ( 2 ) and (−)‐ epi ‐spongistatin 2 ( 23 ) in a ratio of 3.9–2.3:1 (ca.…”
Section: Methodsmentioning
confidence: 99%
“…Andere Synthetiker versuchen, die zielorientierte Synthese mit der Entdeckung und Entwicklung neuer Synthesemethoden zu verbinden. Und schlieûlich gibt es diejenigen, deren Ziel es ist, die Biologie in ihre Totalsyntheseprojekte und Methodenentwicklung zu Croomin [433] [ Martin, 1996] Phorboxazol A [449] [ Batrachotoxinin A [439] [ Barrett, 1996] [ Falck, 1996] FR-90848 [436] [ Neocarzinostatin-Chromophor [447] X = Cl: Spongistatin 1 [453] [ X = H: Spongistatin 2 [454] [ [ Romo, 1998] Pateamin [444] [ Myers, 1998] Salsolenoxid [432] [Paquette, 1997]…”
Section: Ausblickunclassified